Seasonality and outbreak of a predominant Streptococcus pneumoniae serotype 1 clone from The Gambia: Expansion of ST217 hypervirulent clonal complex in West Africa - Antonio, Martin; Hakeem, Ishrat; Awine, Timothy; Secka, Ousman; Sankareh, Kawsu; Nsekpong, David; Lahai, George; Akisanya, Abiodun; Egere, Uzochukwu; Enwere, Godwin; Zaman, Syed MA; Hill, Philip C; et al. (BMC microbiology, 2008)
Streptococcus pneumoniae serotype 1 causes > 20% of invasive disease, among all age groups combined, in The Gambia. In contrast, it is rarely detected in carriage studies. This study compares the molecular epidemiology of S. pneumoniae serotype 1 causing invasive disease in The Gambia between 1996 and 2005 to those carried in the nasopharynx between 2004 and 2006. A total of 127 invasive and 36 nasopharyngeal carriage serotype 1 isolates were recovered from individuals of all age groups and were analyzed by serotyping, antibiotic susceptibility testing and MLST. MLST analysis revealed 23 different sequence types (STs), 18 of which were novel. The most prevalent clone among the 163 isolates was ST618 (70.5%), followed by ST3575 (7.4%), ST2084 (2.5%) and ST612 (2.5%). A single ST (ST618), previously shown to belong to the ST217 hypervirulent clonal complex, was frequent among carriage (61.1%) and invasive (72.7%) serotype 1 isolates. ST618 causing both paediatric and adult disease peaked annually in the hot dry season and caused outbreak in 1997 and 2002. For over a decade, isolates of ST618 have been the dominant lineage among serotype 1 carriage and disease isolates circulating in the Gambia. This lineage shows similar epidemiological features to those of the meningococcus in the African meningitis belt being able to cause outbreaks of disease.